EDUCATION AND THE PERSONAL IDENTITY - Puka, Edi; Beshiri, Dilina (European Scientific Journal, ESJ, 2014)
The human life coincides with a pedagogical itinerary that, if denied, leads to the denial of life itself; in fact, it is not possible for the educative necessities to appear to us as exhaustible, but only as adults, and not always, we are able to realize that the changing exigencies constantly accompany us and correspond to pulsations involving the mind, the body and the interpersonal relations. Humans are all educating persons and they are actually possible to be educated as long as they don’t live isolated or remain abandoned in themselves in the hard efforts to accomplish a continuum of their education, but live instead in a world made of cultures and persons varying from each other. And it is exactly the presence of these diversities and the confrontation among them that provoke strong changing and as a consequence, the exigency of continuous enrichment and growth in the single individuals.